The larva of Allopodagrion brachyurum De Marmels, 2001 (Odonata: Zygoptera: Megapodagrionidae) from Southern Brazil - Neiss, Ulisses Gaspar; Fiorentin, Gelson Luiz; de Marmels, Jürg (Zootaxa, 2011)
The larva of Allopodagrion brachyurum De Marmels, 2001 is the first known for the genus. The larva is described and illustrated based on exuviae of reared larvae collected in the upper course of the Rio dos Sinos, in Caraá município, Rio Grande do Sul, Brazil. The larva of A. brachyurum can be distinguished from all other neotropical megapodagrionid larvae primarily by the presence of a well developed obtuse tubercle in sub-vertical orientation on each side of occiput; two blunt tubercles on top of the head; and caudal gills thin, stiff, triquetral and extremely long, as long as body.